2017
DOI: 10.1007/s10803-016-3025-9
|View full text |Cite
|
Sign up to set email alerts
|

Does the Presence of Anxiety and ADHD Symptoms Add to Social Impairment in Children with Autism Spectrum Disorder?

Abstract: Children with autism spectrum disorder (ASD) experience internalizing and externalizing problems at higher rates than typically developing children, which could worsen social impairment. The present study compared impairment scores (social responsiveness scale, 2nd edition; SRS-2 scores) in 57 children (3-17 years, 82.5% male) with ASD, either with or without heightened levels of anxiety or ADHD symptoms, all per parent report. Children with heightened anxiety problems showed higher scores on four SRS-2 subsca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
55
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 61 publications
7
55
0
Order By: Relevance
“…Internalizing symptoms, including anxiety, phobias, somatization, and excessive worry, are prominent in autism spectrum disorders and can exacerbate primary autism symptom severity (6). Drawing on the triple network model, Hogeveen et al .…”
mentioning
confidence: 99%
“…Internalizing symptoms, including anxiety, phobias, somatization, and excessive worry, are prominent in autism spectrum disorders and can exacerbate primary autism symptom severity (6). Drawing on the triple network model, Hogeveen et al .…”
mentioning
confidence: 99%
“…This might be related to our finding that lower centrality of the left SFG is associated with higher severity of social interaction problems in children with ASD. A previous study also reported that in children with ASD clinical ADHD was associated with increased social awareness deficits (deficits initiating social interaction) but clinical anxiety was not [Factor et al, ]. Among the four groups, the ASD + ADHD group had the highest DC in the left SFG, which was not related to anxiety.…”
Section: Discussionmentioning
confidence: 83%
“…Nonetheless, clinical anxiety and ADHD are commonly experienced by individuals with ASD and are associated with disrupted adaptive functioning and exacerbated social difficulties [Factor et al, ; Kerns et al, , ; Solomon, Miller, Taylor, Hinshaw, & Carter, ; South et al, ; van Steensel et al, ; van Steensel, Bogels, & de Bruin, ]. A recent investigation suggested a twofold increased risk of mortality in patients with mental/behavioral comorbidities and ASD compared with those with ASD only [Schendel et al, ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations